Upaya Moderasi Beragama Pemerintah Desa Mayong Lor, Jepara, Jawa Tengah: Studi pada Pemakaman Umum - Rosyid, Moh; Kushidayati, Lina (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
The purpose of this article is to discuss the efforts of the Mayong Lor Village Government, Mayong Subdistrict, Jepara Regency, Central Java to fulfill the basic needs of indigenous people, namely public cemeteries. Data were obtained through interviews, observations, and literature review and analyzed using a descriptive qualitative approach. The result of the research, the Head of Mayong Lor Village in 2019 decided to make a new cemetery after a Sapta Dharma believer died in 2018. At that time, some Muslim refused to have the deceased be buried in the local village cemetery because the religion column in his KTP was written as penghayat kepercayaan. Some Muslim residents and leaders do not agree if non-Muslim bodies are buried in one cemetery with Muslim bodies. The incident that occurred in 2018 caused a heated debate at that time and was finally buried in another grave in the same village, far from the village. The village government responded to this polemic by opening a new cemetery on village-owned land for interfaith and indigenous believers. This solution is one form of implementation of religious moderation by the village government as mandated by the law. Until now, the cemetery happens to be inhabited by three bodies, a husband, wife, and child (family) who are also Sapta Darma believers.